Influence of Instant Controlled Pressure Drop (DIC) on Allergenic Potential of Tree Nuts - Fatima Vicente; Africa Sanchiz; Rosa Rodríguez-Pérez; Maria Pedrosa; Santiago Quirce; Joseph Haddad; Colette Besombes; Rosario Linacero; Karim Allaf; Carmen Cuadrado (Molecules, 2020)
Pistachio and cashew contain allergenic proteins, which causes them to be removed from the diet of allergic people. Previous studies have demonstrated that food processing (thermal and non-thermal) can produce structural and/or conformational changes in proteins by altering their allergenic capacity. In this study, the influence of instant controlled pressure drop (DIC) on pistachio and cashew allergenic capacity has been studied. Western blot was carried out using IgG anti-11S and anti-2S and IgE antibodies from sera of patients sensitized to pistachio and cashew. DIC processing causes changes in the electrophoretic pattern, reducing the number and intensity of protein bands, as the pressure and temperature treatment increment, which results in a remarkable decrease in detection of potentially allergenic proteins. The harshest conditions of DIC (7 bar, 120 s) markedly reduce the immunodetection of allergenic proteins, not only by using IgG (anti 11S and anti 2S) but also when IgE sera from sensitized patients were used for Western blots. Such immunodetection is more affected in pistachio than in cashew nuts, but is not completely removed. Therefore, cashew proteins are possibly more resistant than pistachio proteins. According these findings, instant controlled pressure drop (DIC) can be considered a suitable technique in order to obtain hypoallergenic tree nut flour to be used in the food industry.